Addressing Potential Conflict Using Participatory Mapping: Collection of Forest Foods From Timber Trees Around Industrial Concessions in Cameroon - Maukonen, Paulus; Donn, Pauline; Snook, Laura K. (Frontiers in Forests and Global Change, 2020)
Extensive areas of Africa’s humid tropical lowland forests have been allocated to timber concessions, but are also inhabited by villagers who obtain resources from the forest. Approximately 61% of timber species in the Congo Basin also yield locally used non-timber forest products (NTFP). Among these are fruits and oil from Moabi (Baillonella toxisperma), and edible caterpillars from Sapelli (Entandrophragma cylindricum) and Tali (Erythrophleum suaveolens). Participatory mapping was used to understand whether logging affects the availability of these food resources to men and women in villages near timber concessions in two areas of Cameroon. Mapping of collection trees and interviews of 20 male and 20 female collectors, in four villages near two logging concessions showed that during one-day collecting trips people walk an average of 2.7 km (± 1.42) to trees where they collect these resources. Food resources are typically collected by both men and women, but men travel further to specific trees, sometimes combining this with hunting excursions further into the forest. Only 15% of the collection trees were located within the logging concessions. However, 72% of Sapelli, 81% of Moabi and 100% of Tali trees from which food resources were collected were larger than their legal felling diameters, meaning that logging could jeopardize the supply of foods from these species. Prioritizing food values over timber values of trees within a certain radius of villages, and excluding them from logging, would safeguard villagers’ access to these food resources. Already, negotiations between villagers and concessionaires have been successful. Many of the mapped collection trees occurred in agroforestry areas delineated by the concessionaire for the use of villagers; another concessionaire had suspended felling of Moabi trees in response to requests by the villagers. However, an extensive and expanding local logging sector on community forests and other lands outside of industrial timber concessions means that negotiations are also needed even within communities, to address the conflicts between obtaining either a one-time financial windfall from felling a tree (usually a male interest); and ensuring ongoing periodic harvests of foods (typically a priority of women, but also of local Baka pygmies).